Destructive Leadership and Psychological Distress in Indonesian Multisector Companies: A Narrative Review Through the Lens of Psychological Safety Theory (2024–2026) - Anang Setiawan (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Destructive leadership is increasingly recognized as a workplace risk that can damage employee well-being, weaken voice behavior, and intensify psychological strain. In Indonesian multisector organizations, leadership-related harm is often discussed through adjacent constructs such as abusive supervision, toxic leadership, hostile leadership climate, and unfair managerial practices. This narrative review examines whether destructive leadership–psychological distress is a recurring phenomenon in Indonesian multisector companies during 2024–2026, and whether Psychological Safety Theory provides a credible explanation for this relationship. The review synthesizes open-access evidence from Indonesian studies and closely related international literature published during the target period, with emphasis on organizations in service, manufacturing, education, hospitality, and mixed-sector settings. Across the reviewed studies, destructive or psychologically unsafe leadership climates are consistently associated with work stress, anxiety, emotional exhaustion, burnout, reduced job satisfaction, lower performance, and withdrawal tendencies. The review finds that the destructive leadership–distress linkage is recurrent enough to warrant serious organizational concern, although direct Indonesian studies using the label “destructive leadership” remain limited. Instead, the strongest evidence appears through studies of toxic work culture, abusive leadership, unsupportive supervision, and low psychological safety. Psychological Safety Theory helps explain why destructive leadership produces distress: when employees do not feel safe to speak up, ask for help, admit mistakes, or challenge unfair treatment, they allocate more cognitive and emotional energy to self-protection than to task accomplishment. The review concludes that the theory remains applicable in Indonesian organizational contexts in 2026, especially when combined with social control perspectives that illuminate fear, silence, and compliance as mechanisms that intensify distress. The article ends with implications, limitations, and future research directions for scholars and practitioners.